Women Stereotypes in The Bell Jar by Sylvia Plath - Salsabila, Mutiara (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2022)
This article aims to explain how the author Sylvia Plath in her novel The Bell Jar reflects a social problem, namely the stereotypes of women. Women stereotypes are a widespread problem and can be found in women's lives. The stereotypes that have been attached to women can then discredit or vilify women in various ways, including those felt by the main female character in this work, Esther Greenwood. This article uses qualitative method and applies feminist theory to analyze the novel, The Bell Jar. This research reveals that women's lives seem to be regulated and labeled by society, especially what is experienced by the main female character in this novel, Esther. Therefore, the article answers questions regarding what are the stereotypes of women shown in the novel The Bell Jar such as 1) women are required to stay at home and only do housework, 2) women are inferior creatures, and 3) women should look beautiful.